2023
DOI: 10.1039/d2sc06340a
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven redox deracemization of indolines and tetrahydroquinolines using a photocatalyst coupled with chiral phosphoric acid

Abstract: The integration of oxidation and enantioselective reduction enables a redox deracemization to directly access enantioenriched products from their corresponding racemates. However, the solution of the kinetically microscopic reversibility of substrates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Weck and Liu developed enzyme-like nanoreactors for the compartmentalization of redox reaction, unfortunately a two-step procedure was still necessary in these instances. Very recently, Liu et al employed an Ir-based photocatalyst to replace the stoichiometric oxidant, and a biphasic system was still required …”
Section: Driven By Chemical Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Weck and Liu developed enzyme-like nanoreactors for the compartmentalization of redox reaction, unfortunately a two-step procedure was still necessary in these instances. Very recently, Liu et al employed an Ir-based photocatalyst to replace the stoichiometric oxidant, and a biphasic system was still required …”
Section: Driven By Chemical Energymentioning
confidence: 99%
“…Very recently, Liu et al employed an Ir-based photocatalyst to replace the stoichiometric oxidant, and a biphasic system was still required. 60 A notable exception without any spatiotemporal separation treatment was described by Zhou et al in 2015 15 (Scheme 8). It was found that NBS oxidation and iridium-catalyzed asymmetric hydrogenation were compatible in one-pot one-step reaction conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Cyclic deracemizations enable the contra-thermodynamic enrichment of one enantiomer from a racemic mixture through the operation of a dissipative cyclic reaction network. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] For example, in the seminal redox-driven cyclic deracemization from Turner and coworkers shown in Figure 1a, 29 enantioselective oxidation of a racemic pair of amines is coupled with non-stereoselective reduction, leading to enrichment in the less reactive of the two amine enantiomers. Concurrent oxidation and reduction is achieved by recourse to an oxidation biocatalyst (monoamine oxidase) that can function in the presence of a reducing agent, in this case ammonia borane (H3N•BH3).…”
mentioning
confidence: 99%
“…To address this critical issue, previous studies have opted to use a single chiral catalyst for deracemization through a two-step process that consists of a nonselective step and a stereodifferentiating step. Notable early studies on redox-driven deracemizations by Toste et al (19) and Zhou et al (20), as well as recent breakthroughs in photochemical deracemization such as Bach et al's seminal works that used enantioselective triplet sensitization (18,(21)(22)(23) and several other elegant systems with reversible C-H bond formation (24)(25)(26)(27)(28)(29), have demonstrated the effectiveness of this approach (30,31). Very recently, Knowles and Miller and co-workers used an elegantly designed tricatalytic system that consisted of one chiral base for C-H bond breakage and a chiral thiol catalyst for C-H bond formation, which exploited the synergistic effect of two chiral catalysts for the photocatalytic deracemization of cyclic ureas (32).…”
mentioning
confidence: 99%
“…( 19 ) and Zhou et al . ( 20 ), as well as recent breakthroughs in photochemical deracemization such as Bach et al .’s seminal works that used enantioselective triplet sensitization ( 18 , 21 23 ) and several other elegant systems with reversible C–H bond formation ( 24 29 ), have demonstrated the effectiveness of this approach ( 30 , 31 ). Very recently, Knowles and Miller and co-workers used an elegantly designed tricatalytic system that consisted of one chiral base for C–H bond breakage and a chiral thiol catalyst for C–H bond formation, which exploited the synergistic effect of two chiral catalysts for the photocatalytic deracemization of cyclic ureas ( 32 ).…”
mentioning
confidence: 99%